Theories of postmodern love a quest for "That which cannot be found" - Szokolyai Dóra (SZTE IEAS Szeged, 2024)
During the postmodern era, between the 1970s and 1990s there has been a large increase in publications on (romantic) love, desire, sexuality, and romance across disciplines, driven by the aim to examine how late-twentieth-century societal shifts (such as the rise of individualism, technological advancements, changing gender roles, and consumerism) have shaped affective economies of romantic experiences. At the same time, the ideal of “true love” has been widely commodified in advertising, popular romance fiction, television shows, songs, magazines, and self-help books. Reflecting on these changes and the pervasiveness of romantic love in culture, theorists in the 1990s identified a “new” form of romantic love: a “postmodern romantic condition” (Illouz 1997). My aim is to connect interdisciplinary approaches (by Eva Illouz, Catherine Belsey, and Anthony Giddens), focusing on the paradoxical relationship between romantic love and postmodernism, which is characterised by an attitude of simultaneous idealisation and ironic self-questioning. I investigate the notion of romantic love as a grand totalizing narrative (Lyotard 1979), reflecting on a postmodern crisis of language where a simple speech act such as “I love you” becomes challenged by the intertextual traces of the past.
Keywords: Bölcsészettudományok; Nyelvek és irodalom